Mineralization of poly(epsilon-caprolactone)/adipate modified starch blend in agricultural soil - Mariani, Pilar D. S. C.; Vinagre Neto, Antonio P.; Silva, Jose P. da; Cardoso, Elke J. B. N.; Esposito, Elisa; Innocentini-Mei, Lucia H. (Springer, 2007)
The biodegradability properties of poly(epsilon-caprolactone) (PCL) and modified adipate-starch (AS) blends, using Edenol-3203 (E) as a starch plasticizer, were investigated in laboratory by burial tests of the samples in previously analyzed agricultural soil. The biodegradation process was carried out using the respirometric test according to ASTM D 5988-96, and the mineralization was followed by both variables such as carbon dioxide evolution and mass loss. The results indicated that the presence of AS-E accelerated the biodegradation rate as expected.
Keywords: biodegradation; poly(epsilon-caprolactone); starch; blends; soil burial